2016
DOI: 10.3892/etm.2016.3106
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations in HIWI level exerts influence on the proliferation of human non-small cell lung cancer cells

Abstract: Abstract. Lung cancer is the leading cause of cancer-associated mortality worldwide, although molecular imaging techniques, including fludeoxyglucose positron emission tomography, have markedly improved the diagnosis of lung cancer. HIWI is a member of the human piwi family, members of which are known for their roles in RNA silencing. HIWI has been shown to serve a crucial function in stem cell self-renewal, and previous studies have reported HIWI overexpression in lung cancers. Furthermore, HIWI has been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The protein and mRNA levels of Hiwi were significantly upregulated in the intra-tumor non-small cell lung cancer (NSCLC) samples. The expression of Hiwi had close relationship with cancer cell proliferation [27]. In pancreatic cancer, on the other hand, altered mRNA expression of hiwi had poorer clinical prognosis [28].…”
Section: Pirnas In Cancermentioning
confidence: 98%
“…The protein and mRNA levels of Hiwi were significantly upregulated in the intra-tumor non-small cell lung cancer (NSCLC) samples. The expression of Hiwi had close relationship with cancer cell proliferation [27]. In pancreatic cancer, on the other hand, altered mRNA expression of hiwi had poorer clinical prognosis [28].…”
Section: Pirnas In Cancermentioning
confidence: 98%
“…Therefore, it was suggested that the PIWIL1 gene could be considered as a molecular target for the treatment of lung cancer, and the use of the PIWIL1 gene silencing technology is considered as a promising treatment [28, 37]. In an investigation, the PIWIL1 expression was manipulated to evaluate its role in the proliferation of NSCLC [38]. Researchers examined the PIWIL1 expression at both levels of protein and mRNA of samples collected from 57 patients with NSCLC by gain of function and loss of function strategies.…”
Section: Piwi Proteins In Lung Cancermentioning
confidence: 99%
“…Researchers examined the PIWIL1 expression at both levels of protein and mRNA of samples collected from 57 patients with NSCLC by gain of function and loss of function strategies. The proliferation of human A549 cell line was also evaluated using colony formation assays and cell counting kit-8 [38]. Results showed that protein and mRNA expression levels of the PIWIL1 had considerably upregulation in NSCLC specimens.…”
Section: Piwi Proteins In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo studies demonstrated that PIWIL1 upregulation contributes to increased tumorigenesis, resistance to chemotherapeutic drugs, acquisition of self-renewal abilities and elevated expression of stem-cell-related transcription markers including octamer-binding protein 4 (OCT4), homeobox protein NANOG (NANOG) and Polycomb complex protein BMI1 ( 41 ). The levels of PIWIL1 protein and transcript were significantly upregulated in intratumor tissue from patients with non-small cell lung cancer (NSCLC), compared with in peritumor tissue ( 42 ). In addition, using gain-of-function and loss-of-function strategies, a positive association between the expression of PIWIL1 and proliferation of the NSCLC cell line A549 was identified ( 42 ).…”
Section: Piwi-pirna In Cancer Developmentmentioning
confidence: 99%